Isolated Thoracoschisis: Case Report and Review of Literature - Hamed Mahmoud Seleim; Mahmoud M.A. ElFiky; Ahmed E. Fares; Mohamed M. Elbarbary (Georg Thieme Verlag KG, 2015)
Abstract A full-term male baby presented at day 2 postnatal with Riedel liver lobe, stomach, and much of the bowel herniating through a thoracic wall defect located just above and lateral to the left nipple. Operative conversion into a gastroschisis-like defect with construction of a silo bag was done. On thorough review of literature, it was found that this is only the second male infant reported with isolated thoracoschisis.